2017
DOI: 10.1038/s41467-017-00854-4
|View full text |Cite
|
Sign up to set email alerts
|

PNLDC1 is essential for piRNA 3′ end trimming and transposon silencing during spermatogenesis in mice

Abstract: Piwi-interacting RNAs are small regulatory RNAs with key roles in transposon silencing and regulation of gametogenesis. The production of mature piwi-interacting RNAs requires a critical step of trimming piwi-interacting RNA intermediates to achieve optimally sized piwi-interacting RNAs. The poly(A)-specific ribonuclease family deadenylase PNLDC1 is implicated in piwi-interacting RNA trimming in silkworms. The physiological function of PNLDC1 in mammals remains unknown. Using Pnldc1-deficient mice, here we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
152
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(165 citation statements)
references
References 38 publications
(61 reference statements)
9
152
1
3
Order By: Relevance
“…Two papers studying the function of PNLDC1 have been published during the revision of this paper [40,41]. Their conclusions are essentially the same as those in our current study; namely, PNLDC1-null mice showed the defects of piRNA 3 0 end trimming, transposon gene silencing, and spermatogenesis.…”
Section: Notesupporting
confidence: 83%
“…Two papers studying the function of PNLDC1 have been published during the revision of this paper [40,41]. Their conclusions are essentially the same as those in our current study; namely, PNLDC1-null mice showed the defects of piRNA 3 0 end trimming, transposon gene silencing, and spermatogenesis.…”
Section: Notesupporting
confidence: 83%
“…Furthermore, the structure of the CB is disrupted, and the localization of MIWI in the CB is lost but not for MILI and MVH in Tdrkh cKO round spermatids [62]. Mechanically, since Tdrkh itself does not contain any nuclease domain, its 3'-trimming might work through recruitment and cooperation with trimmer PNLDC1, which is pivotal for mammalian piRNA 3 -trimming and is essential for transposon silencing and spermatogenesis in mice [63][64][65].…”
Section: Tdrkh/tdrd2mentioning
confidence: 99%
“…Meanwhile, the processing of piRNA precursors into piRNA intermediates is also regulated by the conserved mitochondrial outer membrane protein MITOPLD, which is essential for primary piRNA biogenesis but not secondary piRNA biogenesis [29]. Additionally, as a conserved mitochondrial Tudor domain protein located in IMC, piP-body and MAM structures, TDRKH plays a vital role in piRNA 3' trimming via associating with the trimmer PNLDC1 during fetal piRNA biogenesis [63][64][65] and recruiting MIWI but not MILI to mitochondria in pachytene spermatocytes, therefore revealing that the mitochondria surface serves as a scaffolding for piRNA biogenesis [62].…”
Section: Primary Pirna Processingmentioning
confidence: 99%
“…Three recent studies now show that PNLDC1 is required for piRNA 3′ end formation in mouse testis at different developmental stages. Nishimura et al , Ding et al , and Zhang et al independently revealed that PNLDC1 is required for 3′ end maturation for all (Mili‐, Miwi2‐, and Miwi‐bound) piRNAs.…”
Section: Pirna Biogenesis During Mouse Spermatogenesismentioning
confidence: 99%
“…However, the enzyme that is required for pi RNA 3′ end maturation in vertebrates remained enigmatic. Nishimura et al in this issue of EMBO Reports and two independent studies now identified PNLDC 1 as the exonuclease that is responsible for pi RNA 3′ end processing and transposon silencing during mouse spermatogenesis. Together, these studies establish PNLDC1 as the piRNA 3′ end trimmer in mouse.…”
mentioning
confidence: 97%